Nitric oxide-producing monocyte-myeloid suppressor cells expand and accumulate in the spleen and mesenteric lymph nodes of Yersinia enterocolitica-infected mice - Leporati, Marianela (2024)
Introduction: Yersinia enterocolitica (Ye) is a Gram-negative bacterium that causes gastrointestinal infections. The myeloid-derived suppressor cells (MDSCs) constitute a cellular population with the capacity of inducing the specific suppression of T cells. Although there is evidence supporting the role of MDSCs in controlling the immune responses in several bacterial infections, its role during Ye infection has not yet been reported. Therefore, the purpose of the present work was to analyze MDSCs after oral Ye infection.Methods: C57BL/6 wild-type mice were infected with Ye WAP-314 serotype O:8. The proliferation of splenocytes and mesenteric lymph nodes (MLN) cells was measured as well as the levels of cytokines and nitric oxide (NO) in culture supernatants. The frequency and subsets of MDSCs were analyzed in the intestinal mucosa and spleen by flow cytometry. Furthermore, monocytic-MDSCs (Mo-MDSCs) and polymorphonuclear-MDSCs (PMN-MDSCs) were purified from the spleen of infected mice and their suppressor activity was evaluated in co-cultures with purified T cells.Results: we observed a marked expansion of CD11b+Gr-1+ cells, a phenotype consistent with MDSCs, in the spleen and intestinal mucosa of Ye-infected mice. Interestingly, a robust proliferation of splenocytes and MLN cells was observed only when the MDSCs were depleted or the NO production was blocked. In addition, we determined that only Mo-MDSCs had the ability to suppress T-cell proliferation.Conclusion: Our results highlight a mechanism by which Ye may induce suppression of the immune responses. We suggest that NO-producing Mo-MDSCs expand and accumulate in MLN and spleen of Ye-infected mice. These cells can then suppress the T-cell function without interfering with the anti-bacterial effector response. Instead, these immature myeloid cells may perform an important function in regulating the inflammatory response and protecting affected tissues.